2020
DOI: 10.1007/s11250-020-02410-7
|View full text |Cite
|
Sign up to set email alerts
|

Innovative use and efficiency test of subcutaneous transponders for electronic identification of water buffaloes

Abstract: The objective of this study was to evaluate the viability of using transponders for the electronic identification of water buffaloes and compare their efficiency when used in animals of different age groups. Electronic transponders with RFID technology (2.1 × 12.2 mm) were implanted subcutaneously (D0) in the scutiform cartilage. The animals consisted of four groups: CLF-I (17 calves; 2.1 ± 1.9 months), CLF-II (20 calves; 5.1 ± 3.2 months), HFR (20 heifers; 22 ± 4.7 months) and STR (19 steers; 26.6 ± 6.7 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This growth is essentially related to both the larger number of milked animals and the development of specific technologies for water buffalo farming. These technologies include management strategies Pantoja et al 2018), reproductive techniques (Santos et al 2014;Barros et al 2016;Marin et al 2019), sanitary control (Otaka et al 2017), and processes for electronic animal identification (Garcia et al 2020). In addition, there is growing interest in the buffalo milk quality as it has been increasingly used for dairy product manufacture, due to the high protein and fat contents, which allows higher yields for the dairy industry.…”
Section: History Of Water Buffalo In the Amazon Regionmentioning
confidence: 99%
“…This growth is essentially related to both the larger number of milked animals and the development of specific technologies for water buffalo farming. These technologies include management strategies Pantoja et al 2018), reproductive techniques (Santos et al 2014;Barros et al 2016;Marin et al 2019), sanitary control (Otaka et al 2017), and processes for electronic animal identification (Garcia et al 2020). In addition, there is growing interest in the buffalo milk quality as it has been increasingly used for dairy product manufacture, due to the high protein and fat contents, which allows higher yields for the dairy industry.…”
Section: History Of Water Buffalo In the Amazon Regionmentioning
confidence: 99%
“…Injectable glass tags boast high reliability and safety but are limited in their use on farms due to the difficulty of removing them at the slaughterhouse. It has been demonstrated by Garcia et al that the use of transponders is feasible for the EID of water buffaloes, and they recommended that electronic transponders be implanted in calves that are up to two months of age, as this reduces the physical rate of transponder loss and the loss of functionality [ 87 ]. Kandemir et al employed electronic leg tags (ELT) and electronic ear tags (EET) to identify goats and concluded that the traceability of ear-tagged animals was inferior [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…For buffaloes, the use of subcutaneous transponders that operate in radio frequency (RFId) has been shown to be an efficient, safe, and accurate way of electronic identification, whether for adult or young animals. This technology can be adopted for animals raised in dryland or floodplain pastures, common in the Amazon environment, with an efficiency of 93.9% and 97.2%, respectively (GARCIA et al, 2020).…”
Section: Technologies To Identify Thermal Stress In Water Buffaloesmentioning
confidence: 99%